2021
DOI: 10.3390/plants11010013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two BAHD Acetyltransferases Highly Expressed in the Flowers of Jasminum sambac (L.) Aiton

Abstract: Volatile benzenoid compounds are found in diverse aromatic bouquets emitted by most moth-pollinated flowers. The night-blooming Jasminum sambac is widely cultivated worldwide in the tropics and subtropics for ornamental and industrial purposes owing to its fragrant flowers. Benzylacetate is a characteristic constituent in jasmine scent which makes up to approximately 20–30% of the total emission in the headspace or extract, but the biosynthesis enzymes and the encoding genes have not yet been described. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Although several studies have identified many structural genes involved in the biosynthesis of floral VOCs during jasmine flowering, however, to the best of our knowledge, the regulation of TFs during the formation of jasmine floral aromas has not been confirmed thus far. , In this study, we focused on the identification of potential TFs mediating key odorant biosynthesis and used JsLHY as an entry point to investigate the mechanism underlying how JsLHY regulates the aroma formation of jasmine.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although several studies have identified many structural genes involved in the biosynthesis of floral VOCs during jasmine flowering, however, to the best of our knowledge, the regulation of TFs during the formation of jasmine floral aromas has not been confirmed thus far. , In this study, we focused on the identification of potential TFs mediating key odorant biosynthesis and used JsLHY as an entry point to investigate the mechanism underlying how JsLHY regulates the aroma formation of jasmine.…”
Section: Discussionmentioning
confidence: 99%
“…27 The JsActin2 was used as an internal reference. 14,15,28 The relative expression levels were calculated using the 2 −ΔΔCT method. 29 If not specified, all sequences of primers used in this study are listed in Table S2.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations